Analysis of Street Art Works in the City of Cork: Relationship with the Urban Context and their Legacy - Mitrani, Marina Segarra (E- Revista de Estudos Interculturais, 2026)
The sources discuss different strategies for community and cultural engagement, ranging from institutional alumni relations to urban artistic interventions. KU Leuven presents its global engagement strategy for its 600th anniversary, which utilized large-scale events and digital platforms to reach over 9,000 alumni and raise funds for an international scholarship fund. Similarly, Universidad Miguel Hernández showcases a low-cost, creative approach called "Wit Over Wallet," which uses a 3€ mug as a symbolic "contract" to gamify alumni gratitude and build a loyal "Nice People Club". In contrast, the academic article on street art in Cork analyzes the work of the artist "Finn," who uses analog photography of protests to foster public dialogue. This study explores the ephemeral nature of urban art and its role as a democratic forum for social and political reflection outside traditional institutions